Annex 2 and 3 of the Draft NAMA Text of July 2007: Implications for Bangladesh - Mustafizur Rahman (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
The analysis particularly focuses on the possible implications of Annex 2 and Annex 3 of the NAMA modalities for Bangladesh.
Keywords: F1; 330; Annex 2; 3; NAMA; Implications; Bangladesh